Pembentukan dan karakterisasi kristal cair aceklofenak untuk sistem penghantaran transdermal - Mutiara Zulkarnaini; Erizal Zaini; Rini Agustin (Fakultas Farmasi Universitas Andalas, 2025)
Aceclofenac is a phenylacetic acid derivative classified as a nonsteroidal anti-inflammatory drug (NSAID) used to relieve pain caused by inflammation. It has potential for topical application through a transdermal delivery system. One promising approach is the use of liquid crystals as carriers in transdermal dosage forms. This study aims to develop a simple liquid crystal cream formulation for aceclofenac, using glyceryl monostearate as a mesogen and Pluronic as a stabilizer. The aceclofenac liquid crystal cream was characterized using Polarized Light Microscopy (PLM), Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR), and Differential Scanning Calorimetry (DSC). Evaluations included drug release, permeation, viscosity, flow properties, zeta potential, and freeze-thaw stability. The optimal formulation consisted of oil: glyceryl monostearate–Pluronic P123: water in a 5:15:80% ratio. PLM results showed birefringence and a lamellar phase texture. FTIR analysis confirmed no new chemical bonds, while DSC indicated a reduced melting point and increased enthalpy of fusion. The release and permeation of aceclofenac after 6 hours were 27.849 ± 0.5479 µg/cm² and 21.093 ± 0.5761 µg/cm², respectively—higher than non-liquid crystal preparations. The cream exhibited thixotropic flow behavior, a zeta potential of -50.8 mV, and remained stable after six freeze-thaw cycles. In coclusion, Aceclofenac can be formulated into a liquid crystal cream with glyceryl monostearate as a mesogen, showing a birefringent lamellar phase that enhances its release and permeation